Die Oase Guerrara (Algerische Sahara) - Suter, Karl (ERDKUNDE, 1957)
Guerrara is the remotest of the eight oases of the Mzab. This region is inhabited by Berbers who belong to the Mohammedan sect of the Ibadites. Guerrara (8,400 inhabitants), which is situated on a hill, is a Ksar, i. e. a fortified settlement (town wall and towers). Originating in the 17th century, it has since undergone two extensions. It possesses the largest mosque of the Mzab, a high school, and some modern community buildings (for men) belonging to the kinships. The town's drinking water comes from some wells which may extend as deep down as 40 m. In the former old town these wells can be reached by underground passages from neighbouring houses. When in the past during periods of fighting nobody in the town dared to go to the wells it was possible to raise the water buckets from those passages; the water supply of the town was thus secured. The system of underground passages also made it possible to reach the mosque. Thus, the men of the town could assemble and from there continue the fight. For this reason the mosque possessed storage rooms and a powder magazine in addition to a well. Numerous wells in the palm groves serve for irrigation. At the season when the Oued flows part of the water is held back by an old low dam and is forced to run into the groves. The lanes between the groves serve as ducts and distribute the water, especially to all the wells. During the years 1948—50, the French drilled near Guerrara a 1,200 m. deep artesian well which produces 15,000 litres of water per minute. Since 1954 this water has been led to the groves. Thus, the possibilities of existence have improved considerably.